2011
DOI: 10.1007/s10508-011-9777-6
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Sex Ratio and Birth Order in Early-Onset Gender Dysphoric Adolescents

Abstract: Several sibship-related variables have been studied extensively in sexual orientation research, especially in men. Sibling sex ratio refers to the ratio of brothers to sisters in the aggregate sibships of a group of probands. Birth order refers to the probands’ position (e.g., first-born, middle-born, last-born) within their sibships. Fraternal birth order refers to their position among male siblings only. Such research was extended in this study to a large group of early-onset gender dysphoric adolescents. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(23 citation statements)
references
References 46 publications
2
20
1
Order By: Relevance
“…High sibling sex ratios have been hypothesized to reflect elevated intrauterine testosterone levels, which may be a risk factor for ASD (for more details, see Mouridsen, Rich, & Isager, 2010). In youth samples, a high sibling sex ratio is associated with ASD (Mouridsen et al, 2010) as well as GD in boys (Blanchard, Zucker, Bradley, & Hume, 1995;Schagen, Delemarre-van de Waal, Blanchard, & Cohen-Kettenis, 2012;Zucker et al, 1997) but not GD in girls (Schagen et al, 2012). Future research should consider whether ASD traits are similarly associated with size at birth and sibling sex ratios in gender-referred children.…”
Section: Discussionmentioning
confidence: 99%
“…High sibling sex ratios have been hypothesized to reflect elevated intrauterine testosterone levels, which may be a risk factor for ASD (for more details, see Mouridsen, Rich, & Isager, 2010). In youth samples, a high sibling sex ratio is associated with ASD (Mouridsen et al, 2010) as well as GD in boys (Blanchard, Zucker, Bradley, & Hume, 1995;Schagen, Delemarre-van de Waal, Blanchard, & Cohen-Kettenis, 2012;Zucker et al, 1997) but not GD in girls (Schagen et al, 2012). Future research should consider whether ASD traits are similarly associated with size at birth and sibling sex ratios in gender-referred children.…”
Section: Discussionmentioning
confidence: 99%
“…The new study by Schagen et al (2012) suggests that FBO correlates to certain personality traits which, in turn, correlate to an individual's position on the dominant/insertive-submissive/ receptive axis. Of course, it is possible that a person's position along each of these two axes is a fixed and essential trait, but it is also possible that an individual's position on one axis is fixed at birth, and that his position on the other axis is not, but the fixed characteristic influences the post-natal development of the variable characteristic.…”
mentioning
confidence: 99%
“…According to Schagen et al (2012), there have been 12 previously published studies relating to the relationship between birth order and male transsexualism and, in nine of those studies, the researchers distinguished between two well-recognized male to female transsexual (''MtFs'') phenotypes: androphilic MtFs and gynephilic MtFs. These studies have consistently shown that late FBO is a marker for androphilic MtFs but not for gynephilic MtFs (e.g., Blanchard & Sheridan, 1992).…”
mentioning
confidence: 99%
“…In Schagen et al, although gender dysphoric males had significantly greater numbers of older brothers than controls, they also had significantly fewer older and younger sisters than controls. In addition, both the older and younger sibling sex ratios were significantly elevated in Schagen et al [23]. Thus, none of the prior studies that utilized gender dysphoric youth samples showed a clear and unique relationship between male sexual orientation and the presence of older brothers.…”
Section: Discussionmentioning
confidence: 84%
“…Schagen et al compared the sibship compositions of 95 gender dysphoric and 914 non-clinical control peripubertal females in a Dutch sample [23]. The gender dysphoric females had significantly fewer older siblings, younger brothers, and total siblings.…”
Section: Introductionmentioning
confidence: 99%